Inequality of Opportunity in India: Concepts, Measurement and Empirics. Issue 2 (August 2018) - Motiram, Sripad
In recent times, inequality of opportunity has seen increasing interest among economists and public policy advocates. In this article, I present a critical survey of the idea of inequality of opportunity, including the philosophical ideas that underpin it and the issues and problems that arise in its conceptualization and implementation. I then discuss the operationalization of this idea in the Indian context using two publicly available, nationally representative, secondary statistical databases, namely, National Sample Survey (NSS) and India Human Development Survey (IHDS). Evidence based upon these sources of data suggests considerable inequality of opportunity in India. However, due to limitations of data, there are gaps in our knowledge. I make some suggestions to address these concerns.